2018
DOI: 10.1161/jaha.117.008380
|View full text |Cite
|
Sign up to set email alerts
|

Resource Utilization in Pediatric Patients Supported With Ventricular Assist Devices in the United States: A Multicenter Study From the Pediatric Interagency Registry for Mechanically Assisted Circulatory Support and the Pediatric Health Information System

Abstract: BackgroundFew data exist on resource utilization with pediatric ventricular assist devices (VADs). We tested the hypothesis that device type and adverse events are associated with increased resource utilization in pediatric patients supported with VADs.Methods and ResultsThe Pediatric Interagency Registry for Mechanically Assisted Circulatory Support, a national registry of VADs in patients <19 years old, and the Pediatric Health Information System, an administrative database, were merged. Univariate analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…These authors found, that while not meeting the WTP threshold compared to medical management, CF‐VAD was far superior in cost‐effectiveness to PF‐VAD with sensitivity analyses findings similar to our study: cost of device implantation, long‐term survival, cost per rehospitalization, and utility were important drivers of model conclusion. Our finding that the CF‐VAD capacity for outpatient device support is an important element resulting in higher QALY and lower costs is also mirrored in the literature . Cumulative costs and efficacy after implant for each model are illustrated in Figure where it is illustrated that CF‐VAD enjoys superiority in cumulative QALY across the first year, but bears an upfront cost that is overtaken by PF‐VAD at the end of week 12.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…These authors found, that while not meeting the WTP threshold compared to medical management, CF‐VAD was far superior in cost‐effectiveness to PF‐VAD with sensitivity analyses findings similar to our study: cost of device implantation, long‐term survival, cost per rehospitalization, and utility were important drivers of model conclusion. Our finding that the CF‐VAD capacity for outpatient device support is an important element resulting in higher QALY and lower costs is also mirrored in the literature . Cumulative costs and efficacy after implant for each model are illustrated in Figure where it is illustrated that CF‐VAD enjoys superiority in cumulative QALY across the first year, but bears an upfront cost that is overtaken by PF‐VAD at the end of week 12.…”
Section: Discussionsupporting
confidence: 63%
“…The cumulative costs for CF‐VAD the first year after implant is $1.12M while those of PF‐VAD is $1.39M. While the cost perspective and time horizon of our analysis differ from those of Rossano et al, the rough scale of our financial findings match those previously reported resource requirements in VAD care. This pattern—the cumulative cost for PF‐VAD being lower only in early cycles—explains why CF‐VADs are not cost‐effective if the anticipated length of time a patient needs device support is short.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…20 Similarly, the costs of implantable continuous-flow VADs were taken from a retrospective analysis of PHIS data which also used CCRs. 4 These one-time costs were valued separately from costs of routine healthcare services, check-ups, and other treatments (eg, hospitalizations) borne by pediatric heart failure patients which were derived from previous costeffectiveness analyses. [21][22][23] Healthcare costs include healthcare service delivery (eg, physician and facility fees), medical device, and drug costs.…”
Section: Costsmentioning
confidence: 99%
“…For children who received a VAD, median hospital costs including implantation were estimated to be $750 000, and the median length of stay was 81 days. 4,5 In children with end-stage heart failure, VAD implantation before the patient reaches a state of critical cardiogenic shock is associated with improved outcomes. 6 Beyond this, however, there is very little evidence to further guide the timing of implantation and patient selection in pediatrics.…”
Section: Introductionmentioning
confidence: 99%